Sickness absence in Poland after socio-economic transformation - Zuzanna Szubert (Nofer Institute of Occupational Medicine, 2014)
Background: The aim of the analysis was to determine the magnitude and causes of the sickness-related temporary incapacity for work in Poland, and to identify changes in sickness absence and its differences by the type of economic activity and region. Material and Methods: This analysis is based on the 2006-2012 data on sickness absence compiled from medical certificates of temporary incapacity for work and published by the Social Insurance Institution (Zakład Ubezpieczeń Społecznych). The sickness absence is described in terms of the number of sick leave days relative to the number of the employed or insured people. Results: In 2012, the number of days of disability per one employed was 14.5 (12.1 men, 17.4 women), representing 3.98% of the time lost due to illness. The main causes of absence were: complications of pregnancy and mother's diseases during pregnancy (33% of the sick leave days in women), injury and poisoning (men: 24%; women: 8%), diseases of the musculoskeletal system (men: 17%; woman: 11%). The highest level of sickness absence was noted in the łódzkie, śląskie and warmińsko-mazurskie provinces (38-19% higher than nationwide) and in the administrative and support sectors (22.2 days per 1 employee), when analyzed by sectors of the national economy. Conclusions: The high increase in sickness absence over the recent 7 years due to cancer, mental and muscloskeletal disorders may be an important risk factor for early assessment of permanent incapacity for work. Another major problem is female sickness absence due to pregnancy complications and mother's diseases during pregnancy. Med Pr 2014;65(1):73-84